Parent–child communication and self‐esteem mediate the relationship between interparental conflict and children's depressive symptoms. (19th August 2018) - Ying, Liuhua; Zhou, Huayi; Yu, Shasha; Chen, Chuansheng; Jia, Xuji; Wang, Yanli; Lin, Chongde
Abstract: Background: Previous research has paid little attention to the series mediating effect of parent–child communication and self‐esteem in the relationship between interparental conflict and child outcomes, although several other mechanisms have been found to involve in this relationship. Thus, the purpose of the present study is to test these two factors' serial mediation of the relationship between interparental conflict and children's depressive symptoms in a sample of migrant children in China. Methods: Four hundred thirty‐seven participants from two public schools for migrant children in Zhejiang Province, China, were administered four measures including the Children's Perceptions of Interparental Conflict Scale, the Parent–child Communication Questionnaire, the Global Self‐esteem Scale, and the Centre for Epidemiologic Studies Depression Scale for Children. Results: Results showed that interparental conflict was positively related to depressive symptoms in migrant children, which was partially and serially mediated by parent–child communication and self‐esteem in that order. Conclusions: Parent–child communication and self‐esteem play potential roles in the relationship between interparental conflict and depressive symptoms of migrant children in China. This finding has important implications for psychological service providers working with this group of children or children in similar situations.